2018
DOI: 10.1002/stem.2819
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fusion of Normal and Neoplastic Breast Epithelial Cells with Human Mesenchymal Stroma/Stem Cells Partially Involves Tumor Necrosis Factor Receptor Signaling

Abstract: Formation of hybrid cells by "accidental cell fusion" of normal and neoplastic breast epithelial cells with local tissue-associated mesenchymal stroma/stem-like cells (MSC) in an inflammatory microenvironment can generate new cancer cell populations whereby molecular signaling mechanisms of this process remain unclear. Fusions of lentiviral enhanced green fluorescent protein-labeled MSC with mcherry-labeled breast epithelial cells were quantified and effects of tumor necrosis factor alpha (TNF-α) and receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 41 publications
7
69
0
2
Order By: Relevance
“…Numerous studies further showed that the frequency of cell fusion events was increased upon acute tissue damage or chronic inflammation [7,12,18,32,63,64,[72][73][74][75], which is plausible with regard to efficient BMSC-based and cell fusion-mediated tissue regeneration. BMSCs not only have to be converted into a pro-fusogenic state for subsequent hybridization with target cells but also have to be recruited to the site of tissue damage.…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 96%
See 2 more Smart Citations
“…Numerous studies further showed that the frequency of cell fusion events was increased upon acute tissue damage or chronic inflammation [7,12,18,32,63,64,[72][73][74][75], which is plausible with regard to efficient BMSC-based and cell fusion-mediated tissue regeneration. BMSCs not only have to be converted into a pro-fusogenic state for subsequent hybridization with target cells but also have to be recruited to the site of tissue damage.…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 96%
“…For instance, the fusion of trophoblasts to syncytiotrophoblasts is chiefly regulated by Syncytin-1 and -2, which are transmembrane proteins of retroviral origin [59,60]. Syncytin-1 and -2 are still the best characterized cell fusion mediating proteins in humans, and they might also be involved in human osteoclast fusion [61] and in the fusion of cancer cells with endothelial cells [62,63] or mesenchymal stem cells [64]. In contrast, fusion of myoblasts to multinucleated myofibers depends on remodeling of the actin cytoskeleton and formation of podosome-like structures, which penetrate the target cell, thereby causing the merging of plasma membranes [65,66].…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 99%
See 1 more Smart Citation
“…Mehrere Studien deuten auf einen Zusammenhang zwischen Inflammation/ inflammatorische Mediatoren und Zellfusion hin [19,47,61,65,81,90]. Sowohl Johansson et al als auch Davies et al konnten in tierexperimentellen Studien belegen, dass die Fre quenz von Zellfusionsereignissen in Gegenwart von inflammatori schen Konditionen mitunter bis um den Faktor 100 erhöht war im Vergleich zu entsprechenden Kontrollstudien [19,47].…”
Section: Makrophageunclassified
“…Sowohl Johansson et al als auch Davies et al konnten in tierexperimentellen Studien belegen, dass die Fre quenz von Zellfusionsereignissen in Gegenwart von inflammatori schen Konditionen mitunter bis um den Faktor 100 erhöht war im Vergleich zu entsprechenden Kontrollstudien [19,47]. Speziell für das pro-inflammatorische Zytokin TNF-α konnte ein pro-fusioge ner Effekt beobachtet werden, was sowohl die Fusion von Makro phagen als auch die Fusion von Tumorzellen mit anderen Zellen be trifft [61,65,81,90]. Auch in chronisch entzündetem Gewebe kommt es zu einer erhöhten Frequenz von Zellfusionsereignissen [47,59,69], da die Zellfusion, wie oben erwähnt, eine Rolle in der Geweberegeneration/ Wundheilung spielt und durch inflammato rische Prozesse begünstigt wird.…”
Section: Makrophageunclassified